ABET vs poverty : what have we learned? - Oxenham, John (2004)
Assesses what the experience of the last two or three decades has suggested for planning programmes of adult basic education and training (ABET) that aim to combat poverty and include the skills of literacy and numeracy as important, if not central elements.